Analisis Gaya Bahasa dalam Kumpulan Lagu Idgitaf: Suatu Kajian Stilistika: Analysis of Language Style in Idgitaf’s Song Collection: A Stylistic Study - Nurfadillah Syahrani Rauf; Rosary Iriany; Rusman Latif; Andi Muhammad Nur; Mansur Ga'ga (Universitas Tidar, 2026)
This study aims to determine the linguistic style contained in the Idgitaf song collection. This study is a qualitative study with a descriptive qualitative research design using Geoffrey Leech's stylistic approach, namely cohesion, foregrounding, and cohesion of foregrounding. The object of this study is the songs in the Idgitaf song collection. The main data for this study were sourced from the lyrics of Idgitaf songs, consisting of five songs, namely Terpikat Senyummu, Sekuat Sesakit, Semoga Sembuh, Benar-benar, and Berlagak Bahagia, using observation techniques, namely listening, reading, and note taking. The data analysis technique used the Miles and Huberman model with stages including data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the language styles found in the Idgitaf song collection include 56 language style data found based on the types of language styles from each song lyric with 5 different titles. The data consisted of 2 simile figures of speech (from the lyrics sekuat sesakit), 3 metaphor figures of speech (1 terpikat senyummu, 1 berlagak bahagia, 1 sekuat sesakit), 7 personification figures of speech (1 terpikat senyummu, 3 berlagak bahagia, 1 benar-benar, 1 semoga sembuh, 1 sekuat sesakit), 3 paradoxes (2 berlagak bahagia, 1 semoga sembuh), 2 hyperboles (1 berlagak bahagia, 1 benar-benar), 18 parallelisms (4 terpikat senyummu, 3 berlagak bahagia, 5 benar-benar, 3 semoga sembuh, and 3 sekuat sesakit), 2 ellipsis styles (1 terpikat senyummu, 1 benar-benar), 14 repetition styles (1 terpikat senyummu, 3 berlagak bahagia, 3 benar-benar, 3 semoga sembuh, and 4 sekuat sesakit), 5 rhetorical style (2 terpikat senyummu, 1 benar-benar, 1 semoga sembuh, and 1 sekuat sesakit).